2023
DOI: 10.1002/bit.28432
|View full text |Cite
|
Sign up to set email alerts
|

Development of an aminotransferase‐driven biocatalytic cascade for deracemization of d,l‐phosphinothricin

Abstract: Abstract2‐oxo‐4‐[(hydroxy)(methyl)phosphinoyl]butyric acid (PPO) is the essential precursor keto acid for the asymmetric biosynthesis of herbicide l‐phosphinothricin (l‐PPT). Developing a biocatalytic cascade for PPO production with high efficiency and low cost is highly desired. Herein, a d‐amino acid aminotransferase from Bacillus sp. YM‐1 (Ym DAAT) with high activity (48.95 U/mg) and affinity (Km = 27.49 mM) toward d‐PPT was evaluated. To circumvent the inhibition of by‐product d‐glutamate (d‐Glu), an amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
1
2
0
Order By: Relevance
“…As summarized in Table , the K m value of ( R )- Ach AT was 14.20 mM, indicating its high affinity to the D-PPT. The k cat /K m value of ( R )- Ach AT was 2.01 × 10 3 s –1 M –1 , which was comparable to that of reported Ym AT (2.04 × 10 3 s –1 M –1 ) and 2.09 fold higher than that of reported Rg DAAO (0.96 × 10 3 s –1 M –1 ), indicating the significant advantage of catalytic efficiency of ( R )- Ach AT toward D-PPT. For ( S )- Ab AT, the K m and k cat values of PPO were 22.8 mM and 15.81 s –1 , respectively.…”
Section: Resultssupporting
confidence: 66%
“…As summarized in Table , the K m value of ( R )- Ach AT was 14.20 mM, indicating its high affinity to the D-PPT. The k cat /K m value of ( R )- Ach AT was 2.01 × 10 3 s –1 M –1 , which was comparable to that of reported Ym AT (2.04 × 10 3 s –1 M –1 ) and 2.09 fold higher than that of reported Rg DAAO (0.96 × 10 3 s –1 M –1 ), indicating the significant advantage of catalytic efficiency of ( R )- Ach AT toward D-PPT. For ( S )- Ab AT, the K m and k cat values of PPO were 22.8 mM and 15.81 s –1 , respectively.…”
Section: Resultssupporting
confidence: 66%
“…1 b). Based on our previous report (Liu et al 2023 ), the Ym DAAT exhibited high activity (48.95 U/mg) and affinity ( K m = 27.49 mM) towards D-PPT. Thus, Ym DAAT was employed to catalyze the amino transformation between D-PPT and PPO, followed by L-PPT synthesis catalyzed by Pt TA.…”
Section: Resultsmentioning
confidence: 68%
“…The asymmetric synthesis of L-PPT from 4-(hydroxy(methyl)phosphoryl)-2-oxobutanoic acid (PPO) catalyzed by fold-type I TAs with 100% theoretical yield and strict ( S )-enantioselectivity has continuously attracted the interest of researchers (Cheng et al 2021 ; Horsman and Zechel 2017 ). However, several TAs developed for the asymmetric synthesis of L-PPT suffered low equilibrium constant, resulting in an unfavorable thermodynamic equilibrium, which further led to the inability to achieve the theoretical yield (Liu et al 2023 ; Zhu and Hua 2009 ), for example, the TA from Citrobacter koseri ( Ck TA), which showed a maximum conversion of 93.3% at 100 mM substrate concentration (Jia et al 2019 ), and the TA from Pseudomonas fluorescens ( Pf TA), which we previously reported to yield 79% L-PPT after 24 h reaction at 500 mM substrate (Jin et al 2019 ). Removal of by-product can effectively shift the equilibrium in the transamination reaction, one of the most attractive strategies was to construct an enzymatic cascade by coupling amino acid dehydrogenases (AADHs, EC 1.4.1.X) (Hepworth et al 2017 ; Mathew et al 2023 ), such as alanine dehydrogenase (AlaDH, EC 1.4.1.1) or glutamate dehydrogenase (GluDH, EC 1.4.1.2) (Wu et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%